Clinical Prescription-Protein-Small Molecule-Disease Strategy (CPSD), A New Strategy for Chinese Medicine Development: A Case Study in Cardiovascular Diseases - Guo, Yong-Zhi; Jiang, Ying-Nan; Li, Yi-Fang; Kurihara, Hiroshi; Dai, Yi; He, Rong-Rong (Frontiers in Pharmacology, 2020)
Chinese medicine is a national treasure that has been passed down for thousands of years in China. According to the statistics of the World Health Organization, there are currently four billion people in the world who use Chinese medicine to treat diseases, accounting for 80% of the world’s total population. However, the obscurity of its theory, its unmanageable quality, its complex compositions, and the unknown effective substances and mechanisms are great obstacles to the internationalization of Chinese medicine. Here, we propose a new strategy for the development of Chinese medicine: the clinical prescription (C)-protein (P)-small-molecule (S)-disease (D) strategy, namely the CPSD strategy. The strategy uses clinical prescriptions as the source of medicine and uses computer simulation technology to find small-molecule drugs targeting therapeutic proteins for treating specific diseases so as to deepen awareness of the value of Chinese medicine. At the same time, this article takes cardiovascular drug development as an example to introduce the application of CPSD, which will be instrumental in the further development, modernization, and internationalization of Chinese medicine.